PERSPEKTIF HUKUM ISLAM TERHADAP TRANSAKSI JUAL BELI ONLINE DENGAN MODEL PERIKLANAN - Wahida Z (AL-ILMU, 2022)
Buying and selling with an advertising model in e-commerce is carried out by carrying out the procedures and conditions that have been given, starting from registering, following the requirements, and carrying out the buying and selling process with buyers being able to shop according to the desired goods, just choose, and make payments either by transfer or payment on the spot after later the goods will be sent via a delivery service. After payment is made, the e-commerce will automatically verify and confirm shortly thereafter. A confirmation will usually be sent to your mobile number and email, including any new developments such as tracking numbers and delivery of goods. The agreement occurs when the transaction offer sent by the buyer has been received and approved by the recipient. A review of Islamic law on buying and selling online, can be legal and illegal. It is invalid if the information provided at the time of the contract is different from the reality after an item is shown so that the buyer becomes disappointed. If in practice there is a condition that always disappoints the buyer, buying and selling is prohibited, because there is an element of fraud and unwillingness in the buying and selling process which is one of the pillars of buying and selling, but when the information at the time of the contract is in accordance with the reality at the time of the goods it is submitted, then such a sale and purchase is valid. If the transaction takes place at the same time while both parties are located far apart, this can be applied to transactions via telephone or cell phone, then the consent and qabul that occur are direct as if they were both in one place, the contract is considered to have occurred when the goods were given.